Physical fitness profile in elite beach handball players of different age categories - Lemos, L. F.; Oliveira, V. C.; Duncan, M. J.; Ortega, J. P.; Martins, C. M.; Ramirez-Campillo, R.; Sanchez, J. S.; Nevill, A. M.; Nakamura, F. Y. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The aims of this study were to compare anthropometric and fitness variables of high-level beach handball players across Under-19 (U-19), Under-21 (U-21) and senior male categories, and between male and female senior players; and to test the correlations among those measures. METHODS: A total of 70 high-level players (53 male of different ages) were evaluated for 5-m acceleration, 15-m sprint, horizontal jump, handgrip strength, specific beach handball throwing velocities, and anthropometric variables. Differences between age groups were tested using ANOVA. Independent t-test was used to compare fitness variables between male and female elite athletes, and Pearson partial correlation coefficients were calculated between each of the fitness variables using BMI and age as covariates. SPSS Software was used, and the level of significance was set at 95%. RESULTS: The U-21 athletes better performed on horizontal jump and 6-m throw than the U-19 athletes. Senior athletes showed better performance on horizontal jump than U-19 athletes (P=0.05). Positive correlation was seen for handgrip on dominant and non-dominant hands and 6-m throwing speed, and for handgrip on dominant hand and inflight velocity (P=0.05). Negative correlations were observed between horizontal jump and 5-m acceleration, and 15-m sprint (P=0.01 and P=0.05, respectively). CONCLUSIONS: Male athletes better performed than women in all the fitness tests. The study, for the first time, showed physical fitness comparisons between beach handball elite male athletes of different ages and between genders. These are key steps for coaches and athletes and may support future beach handball studies and practice.